Societal reaction to the release of sex offenders - Bata, Samantha (My University, 2019)
This qualitative study explored public views on the release of convicted sex offenders. A content analysis was conducted on the comments section of four newspaper articles about releases. One hundred and fifty-six comments were examined, and six prominent themes emerged including: Critiques of the criminal justice system, execution, life imprisonment, tattooing, race and physical disfigurement. Most comments were negative and voiced a desire for harsher punishment. Public perception of sex offenders largely reflected stereotyped media portrayals.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: sex offenders; public opinion